INCREASING ACTIVITY AND LEARNING OUTCOMES OF MATHEMATICS ABOUT FRACTIONS THROUGH MATHEMATICAL LITERACY IN CLASS VI STUDENTS OF SD NEGERI NAMPUDADI - Komariyah, Komariyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The low learning outcomes of mathematics and student activity encourage researchers to conduct this research. The purpose of the study is to obtain information about whether or not the use of mathematical literacy increases student activity and learning outcomes. This study uses a classroom action research approach. Subject 27 students. Data collection techniques with tests, observations, and interviews. Data analysis techniques with critical analysis techniques and comparative descriptive techniques with data validity namely triangulation and key informant review. The results of the study, in the initial study of students who completed 19%, the first cycle was 49%, and the second cycle was 100%. The activeness of students in the initial study was 37%, in the first cycle 74%, and in the second cycle 100%. The use of mathematical literacy has been proven to improve student learning outcomes in mathematics learning about fractions in grade 6 students of SDN Nampudadi.